The bride test - Hoang, Helen 1982 - (Corvus, 2019)
"From the critically acclaimed author of The Kiss Quotient comes a romantic novel about love that crosses international borders and all boundaries of the heart... Khai Diep has no feelings. Well, he feels irritation when people move his things or contentment when ledgers balance down to the penny, but not big, important emotions--like grief. And love. He thinks he's defective. His family knows better--that his autism means he just processes emotions differently. When he steadfastly avoids relationships, his mother takes matters into her own hands and returns to Vietnam to find him the perfect bride. As a mixed-race girl living in the slums of Ho Chi Minh City, Esme Tran has always felt out of place. When the opportunity arises to come to America and meet a potential husband, she can't turn it down, thinking this could be the break her family needs. Seducing Khai, however, doesn't go as planned. Esme's lessons in love seem to be working...but only on herself. She's hopelessly smitten with a man who's convinced he can never return her affection. With Esme's time in the United States dwindling, Khai is forced to understand he's been wrong all along. And there's more than one way to love"--